EARLY DIAGNOSIS AND PREVENTION OF BENIGN BREAST DISEASE IN THE PRACTICE OF OBSTETRICIANS -GYNECOLOGISTS - Gromova, A.M.; Liakhovska, T.Iu.; Dobrovolska, L.M.; Gromova, A.L.; Baklanova, O.L. (World of Medicine and Biology, 2012)
The analysis of the incidence of benign dyshormonal breast diseases was managed. 6076 surveys of mammary glands were carried out during 2009-2011. Diagnosis was based on inspection, palpation, mammography, ultrasound scanning, puncture of the nodules and cytology. The diffuse form of the diseases were accounted for 77.9%, nodal - 8%, cyst - 5.6%, fibroadenoma - 3.7%, tumors - 4.4%. The task of obstetrician-gynecologist is the timely detection of early signs of breast pathology, in-depth examination of the interaction with related professionals for providing timely treatment.
Keywords: mammary gland; breast; diagnosis; prevention